Discovery of Natural Products Possessing Selective Eukaryotic Readthrough Activity: 3‐epi‐Deoxynegamycin and Its Leucine Adduct. Issue 10 (9th July 2014) - Taguchi, Akihiro; Hamada, Keisuke; Kotake, Masaya; Shiozuka, Masataka; Nakaminami, Hidemasa; Pillaiyar, Thanigaimalai; Takayama, Kentaro; Yakushiji, Fumika; Noguchi, Norihisa; Usui, Takeo; Matsuda, Ryoichi; Hayashi, Yoshio
Abstract Herein we report the first discovery of natural readthrough products that do not display antimicrobial activity. Two natural negamycins, 3‐epi‐deoxynegamycin and its leucine adduct, isolated 37 years ago, were found to be potent readthrough agents against nonsense mutations of eukaryotes, but not prokaryotes, without displaying antimicrobial activity. These results suggest that the compounds are valuable leads for the development of readthrough drugs against nonsense‐mediated genetic diseases without the potential for contributing to the emergence of drug‐resistant bacteria.